2015
DOI: 10.1186/s12879-015-0964-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and its relationship with non-adherence to TB treatment: a multicentre study

Abstract: BackgroundThe successful cure of tuberculosis (TB) is dependent on adherence to treatment. Various factors influence adherence, however, few are easily modifiable. There are limited data regarding correlates of psychological distress and their association with non-adherence to anti-TB treatment.MethodsIn a trial of a new TB test, we measured psychological distress (K-10 score), TB-related health literacy, and morbidity (TBscore), prior to diagnosis in 1502 patients with symptoms of pulmonary TB recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 34 publications
3
80
1
7
Order By: Relevance
“…Lastly, patient expectations, which are usually "total cure, " cannot be met in case of mucocutaneous involvement (12). Poor understanding of the illness and psychological distress may also be related to nonadherence to treatment regimens in females (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, patient expectations, which are usually "total cure, " cannot be met in case of mucocutaneous involvement (12). Poor understanding of the illness and psychological distress may also be related to nonadherence to treatment regimens in females (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Though awareness on TB was good in an Indian urban slum population, information on access to proper medical care was not known (Chinnakali et al, 2013). It is suggested that TB patients with low health related literacy had higher psychological distress (Theron et al, 2015). Thus it appears that health literacy, morbidity due to TB and psychological well-being are interlinked.…”
Section: Psychological Interventions and Their Effect On Tuberculosismentioning
confidence: 99%
“…A number of factors, including social stigmatization, financial situation, malnutrition, human immunodeficiency virus (HIV)‐coinfection during treatment, and TB misconceptions and treatment adherence are associated with a lower chance of recovery from TB . Adherence itself is influenced by the type of regimen‐specific setting, financial status, social and behavioral factors, and the presence of caregivers, but many now consider that it may be strongly mediated by the effects of comorbid depression …”
Section: Association Between Depression and Tbmentioning
confidence: 99%
“…[35][36][37][38] Adherence itself is influenced by the type of regimen-specific setting, financial status, social and behavioral factors, and the presence of caregivers, 39,40 but many now consider that it may be strongly mediated by the effects of comorbid depression. 19,41 Reciprocally, the high prevalence of depression among patients with TB may be associated with non-adherence to TB treatment because of adverse effects. 42,43 Several medications used in TB treatment have notable adverse psychiatric effects.…”
Section: Risk Factorsmentioning
confidence: 99%